(untitled) (Biological Sciences - PJSIR, 2023)
Micronutrient deficiency (manganese, copper, zinc, iron and boron) appears to have become more prevalent in crops in recent years. A field experiment was carried out to examine the response of application of foliar commercial micro-nutrients mixture "Uni Micropower" (zinc 4.7%, iron 2%, manganese 2%, boron 1.0% and copper 0.3%) on wheat in 2015-16. Treatments included, control and Uni Micropower spray at tillering, jointing, booting, milking, tillering + jointing, tillering + booting, tillering + milking, jointing + booting, jointing + milking, booting + milking, tillering + jointing + booting, tillering + jointing + milking, tillering + booting + milking and tillering + jointing + booting + milking stage. The results indicated that treatments significantly enhanced plant height, grains/spike, 1000 grain weight, biological yield, grain yield, harvest index, grain protein and carbohydrate contents. The maximum grain yield, quality and economic return were recorded when Uni Micropower sprays were applied at tillering, jointing, booting and milking stage. In conclusion, Uni Micropower foliar spray is helpful to improve the quality and production of wheat.